Literature review on the activity of kepuh plant (Sterculiafoetida L.) as a natural antioxidant - Dewi Kurnia; Asep Roni; Kiki Dwi Rahayu (Journal of Agritechnology and Food Processing, 2024)
Kepuh (Sterculiafoetida L.) is a traditional medicinal plant that is a source of secondary metabolites, also known for its phenolic content as an antioxidant and antibacterial.   The kepuh plant has been scientifically proven to have anti-inflammatory and analgesic activities. The preparation of this literature review aims to provide information on the efficacy of the kepuh plant as an antioxidant. The methods used to test the antioxidant activity of kepuh are DPPH (1,1-diphenyl-2-picrylhydrazyl) and ABTS (2,2-Azinobis-3-ethyl benzhothiazoline-6-sulfonic acid). Antioxidant activity is determined from the IC50 value. Where, the lower the IC50 value, the stronger the antioxidant activity of a sample.  The conclusion from this literature search is that kepuh is a plant that has strong antioxidant activity.